Economy, Anti-Economy, Underground Economy: Conceptual and Terminological Problems - Gylys, Povilas (Ekonomika, 2005)
This paper discusses conceptual and terminological problems stemming from the lack of discipline in the field of exploration of the economic phenomena reflecting the unregulated practices, practices of non- compliance with the official order and cases of production of economic bads and loss of existing wealth. The resulting conceptual and terminological proposals are aimed at improving the structurization, formalization of economic knowledge and thereby quality of communication inside the economic profession as well as between economists and general public. The research is based on the principles (assumptions) of the holistic paradigm.